Understanding the Uniqueness of Hebephrenic Schizophrenia: A Case Study: Memahami Keunikan Skizofrenia Hebefrenia: Studi Kasus - Sadira, Layyina; Fitriana, Qurrota A’yuni (Universitas Muhammadiyah Sidoarjo, 2024)
This clinical case study explores the uniqueness of the case and the challenges of diagnosis in a hebephrenic schizophrenia patient at RSJ X Malang. The subject was a 32-year-old woman with a history of aggressive and erratic behaviour, assessed over a period of 2 weeks through comprehensive psychological assessment, namely autoanamnesis, alloanamnesis, and daily observation. The methodology used was qualitative methodology with a case study approach to find out the uniqueness of the case in depth. This study identifies the psychopathological features and challenges of patients with hebephrenic schizophrenia. The subject exhibited typical symptoms of hebephrenic schizophrenia, onset of the disorder between the ages of 15-25 years and disorganisation in thought processes. In addition, the subject fulfils the main diagnostic criteria of schizophrenia, namely the presence of thought eco, disconnected thought flow, and dull emotions. Delusions and hallucinations were not apparent during the examination. This case is expected to provide insight into the complexity of the disorder, especially the challenges faced in subjects with hebephrenic schizophrenia so that it can be a useful input for the subject's support system.